Usability: key characteristic of software quality - Đorđević, Nebojša D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper emphasizes the importance of software usability as a key quality characteristic of software during its use. At the beginning of the paper, a retrospective of formal definitions of usability is given in order to show the evolution of views on usability for more than three decades. To ensure the required quality in use, it is necessary to measure and evaluate many characteristics that affect the usability of software. The paper gives a brief chronology of attempts to identify different dimensions of usability based on its definitions. Since it is not easy to determine the characteristics that contribute most to the quality in use, two methods are applied in identifying the key attributes that affect usability, and they are to be given special consideration when building a model of usability.